HPV e doenças coronarianas em mulheres no climatério - GRANJA, Andr[ea de Neiva (2023)
Introduction: Cervical cancer is associated with high-risk HPV strains, as well as high-risk HPV infection is associated with coronary artery disease in women. Furthermore, in the climacteric period in women, menopause is associated with chronic inflammation and has major implications for the development of CAD and associated lipid disorders. Thus, the association of HPV with coronary artery disease in climacteric women needs to be further studied. Objective: To study the relationship between HPV infection and coronary heart disease in climacteric women. Methods: This was a quantitative, descriptive and analytical study, carried out through the application of sociodemographic questionnaires. Clinical examination consisting of blood pressure and BMI calculation; the detection and genotyping of HPV from cervico-vaginal samples of the patients occurred by extracting the total DNA with a commercial kit, then they were submitted to nested PCR reactions to detect the HPV. Positive samples were sequenced on a MegaBACE 1000 automated sequencer and chromatograms were analyzed with software. Biochemical analyzes were of glucose, glycated hemoglobin, triglycerides, total cholesterol, HDL and LDL. And the results were analyzed in GraphPad Prism 7.0 using Fisher or Χ2 tests, which were considered significant when p<0.05. Results: 71 patients were included in the study, most of whom were under 60 years old, almost half of the patients had an income equal to or less than 1 minimum wage. Almost all the patients lived in the city of São Luís, were overweight or had varying degrees of obesity, normal levels of triglycerides and total cholesterol, HDL below desirable values and LDL within normal values. In addition, increased levels of glycated hemoglobin, but less than half had high fasting blood glucose. Viral DNA was found in just over a third of the patients, among the 22 patients with HPV, almost 60% had high oncogenic risk HPV, with HPV16 being the most frequent genotype. Of the patients, almost half were hypertensive and just over a third of the patients were diagnosed with CAD. There was a highly significant association (p=0.001) between the patients' age and the presence of CAD, more frequently in older patients, between hypertension and CAD, more frequently in hypertensive patients, CAD was more common among patients with high fasting blood glucose and most patients with HPV had CAD. Conclusion: The proportion of patients infected with HPV in groups with and without coronary artery disease (CAD) was determined, verifying that the infection is significantly more frequent in women with CAD, which supports the hypothesis that HPV contributes to the CAD risk. The different HPV genotypes (high risk versus low risk) showed no significant association with CAD. There was an association of CAD with hypertension and older age. Furthermore, they tended to present higher values of glycemia and glycated hemoglobin, but without significant differences and did not present changes in their lipid profile. Additional studies involving cellular and animal models are needed to determine the mechanisms by which HPV may contribute to the pathogenesis of CAD.